2019
DOI: 10.15171/ps.2019.36
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Propolis and Probiotic Lactobacillus acidophilus against Carbon Tetrachloride-Induced Hepatotoxicity in Rats

Abstract: Background: Propolis (PRS) and probiotic bacteria Lactobacillus are natural products used as dietary supplement for their therapeutic benefits. This study was performed to examine the possible hepatoprotective effect of PRS and probiotics (PRCs) against carbon tetrachloride-induced liver injury. Methods: Experimentally, intoxicated rats received 0.5 ml/kg CCl4 (i.p.) daily for six days, pretreated rats received per os PRS 100 mg/kg or PRCs 109 CFU for six days followed by a single dose of 0.5 ml/kg CCl4. Contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
3
1
0
Order By: Relevance
“…Results obtained in this study are in good agreement with what obtained by Oumeddour et al . ( 2019) who showed that treatment with CCl 4 resulted in a major de ciency in the liver catalase of the enzymatic antioxidant defense mechanism, Also Heeba and Mahmoud (2014) showed that no signi cantly increase when rats treated with CCl4.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Results obtained in this study are in good agreement with what obtained by Oumeddour et al . ( 2019) who showed that treatment with CCl 4 resulted in a major de ciency in the liver catalase of the enzymatic antioxidant defense mechanism, Also Heeba and Mahmoud (2014) showed that no signi cantly increase when rats treated with CCl4.…”
Section: Discussionsupporting
confidence: 93%
“…Results obtained in this study are in the same line with Salatin et al (2019), andOumeddour et al (2019) they are also in accordance with Fahmy et al(2016) and Al-Sayed et al . ( 2015) stated that CCl 4 increases biochemical parameters such as AST, ALT, urea and creatinine serum levels.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…S. boulardii was able to improve the tissue antioxidant status and inhibit neutrophil recruitment, thereby reducing intestinal damage and associated hepatitis ( 134 ). A reduction of oxidative damage in hepatocytes by probiotics was also reported by Oumeddour et al ( 135 ).…”
Section: Probiotics and Their Protective Effectssupporting
confidence: 76%